MOTIVES OF PROSPECTIVE STUDENTS’ RESOLVE TO STUDY AT THE HIGHER EDUCATION INSTITUTION - Bubnys, Remigijus; Bakanovienė, Tatjana; Bivainienė, Lina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
In today’s world, the choice of a profession and professional career planning are becoming very important processes in young persons’ life, during which they make a decision, influencing their future. The first real encounter with the problem of the career choice takes place at school, when a student has to choose study subjects or an educational profile. Later, future students analyse what study programme or higher education institution to choose. There are numerous reasons and factors determining graduates’ choice. The aim of the conducted study is to disclose prospective students’ motives, choosing the study programme and the higher education institution (in this case, Siauliai University in Lithuania). The applied research method is an online survey, using a semi-structured questionnaire. Research results also disclose the quality of providing information about studying possibilities. According to the research results, prospective students clearly knew in which higher education institution they would study and what specific programme they would choose. The main source of information choosing studies was information provided on the website of the institution; friends’ recommendations were also relevant. Choosing a particular higher education institution, the main motives were personal and the ones directly related to the higher education institution: the wish to study close to home, urban infrastructure, the learning environment and teachers. The choice of a concrete study programme was determined by early career dreams, attractiveness and interest of the study programme as well as employment opportunities.